ESTIMATION OF GENETIC PARAMETERS IN SORGHUM UNDER THE EFFECT OF POPULATIONS AND PLANTING SEASONS. - & et al., Wuhaib (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In order to estimate the phenotypic, genotypic and environment variance; and estimate the genotypic and phenotypic coefficient variations; and heritability broad sense. for some traits, in sorghum(Sorghum bicolor L. Moench).Experiment was carried out at the field of Field Crop Dept. College of Agric. Univ. of Baghdad, during Spring and Fall season of 2013, by using split plot arrangement in randomize complete block design with four replications . The population densities are 6000, 7000, 80000 p.ha-1.as the main plots. Traits and variances were recorded on three genotypes of sorghum, Enqath, Rabih and Kaffieras sub plots. Results of statistical analysis showed that the cultivar Enqath the higher yield 5.81 ton.ha-1. and 6.13 ton.ha-1. for Spring and Fall season respectively. This was due to superiority in weight of 1000 grain 32.48g in spring, and no. of grains 2323 grains for Fall. The better population density was 60000 .ha-1. for spring due to highest of grain weight, no. of grains and dry weight for its increase in functional no. of leaves and flag leaf area. In Fall the plant in this population were give higher yield due to superiority in dry weight, leaf area index, grain weight and flag leaf area. The superior cultivar and population characterized in lower leaf area and day to maturity and higher in harvest index. So these traits characterized with higher of genetic variation and heritability.